2022
DOI: 10.1149/1945-7111/ac9bdf
|View full text |Cite
|
Sign up to set email alerts
|

A One-Dimensional Model of a PEM Fuel Cell with the Cathode Catalyst Layer Hydrophobically Treated for Water Management

Abstract: A proton exchange membrane (PEM) fuel cell with a hydrophobically treated cathode catalyst layer (CL) demonstrates ~220% peak power increase with humidified air at 70°C. To understand the reasons for the increase, a mathematical model was developed focusing on the oxygen-water two-phase transport phenomena. The model suggests the treatment affects the CL in two ways. First, the interface of the ionomer layer exposed to the gas pores becomes more hydrophobic, facilitating less coverage and faster water drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, our in-situ ECSA measurement reveals that the hydrophobic treatment has minimal influence on the cathode's ECSA (a Pt in Equation ( 2)). 10 Therefore, Equation (2) shows that the only possible reason for the fuel cell improvement in the kinetic-controlled region is related to the oxygen concentration in the ionomer near the catalyst surface (C O ), which is supposed to be determined by the oxygen solubility in the Nafion ionomer phase. The oxygen solubility in the ionomer phase is found to be inversely affected by the hydration level of the ionomer phase.…”
Section: Nanostructure Modification In the Normal Direction Of The Su...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our in-situ ECSA measurement reveals that the hydrophobic treatment has minimal influence on the cathode's ECSA (a Pt in Equation ( 2)). 10 Therefore, Equation (2) shows that the only possible reason for the fuel cell improvement in the kinetic-controlled region is related to the oxygen concentration in the ionomer near the catalyst surface (C O ), which is supposed to be determined by the oxygen solubility in the Nafion ionomer phase. The oxygen solubility in the ionomer phase is found to be inversely affected by the hydration level of the ionomer phase.…”
Section: Nanostructure Modification In the Normal Direction Of The Su...mentioning
confidence: 99%
“…One method is to mix hydrophobic PTFE in the catalyst ink, of which details, advantages, and disadvantages have been discussed in the previous publications. 9,10 In this work, we would like to discuss another approach, the direct modification of Nafion ionomer' structure. 11,12 Prior works 12,13 have shown that the surface hydrophobicity of the PFSAbased ionomer phase can be increased by modifying its surface composition to have more of the hydrophobic fluorocarbon backbone and less of the hydrophilic sulfonic acid groups.…”
mentioning
confidence: 99%